HUBUNGAN PANJANG BOBOT DAN REPRODUKSI IKAN KEMBUNG LELAKI Rastrelliger kanagurta (Cuvier, 1817) DI PERAIRAN SELAT MALAKA TANJUNG BERINGIN SERDANG BEDAGAI SUMATERA UTARA - Julia Syahriani Hsb; Mohammad Basyuni; Ani Suryanti (AQUACOASTMARINE, 2015)
Activities the continuous mackerel of catch will be decreasing fish stock in the nature. The research aims to know relationship among length weight, factor of condition, reproductive, first size riping ovum and apex spawning of mackerel. This research was conducted in Malacca strait Tanjung Beringin Serdang Bedagai from March until May 2015 based on the location of fishing by fishermen divided into three stations at a distance of 3.704 meters from the beach and the distance between each station was 1.852 meters. Water and fish sampling was carried out for one month. The results showed that length weight was positive allometric. Factor conditions were 1,12 – 1,18 and classified as less flat. Sex ratio of fish was ideal conditions. Value of gonad maturation index between female was 2,87% and male was 2,18% respectively. Fecundity was 30.250 – 57.240 granule. First size riping ovum is 164 – 170 mm. The mackerel has a apex spawning in April.Keywords : Mackerel, Spawning, Factor condition, Ovum